You are on page 1of 37

# Chapter 1- Complex numbers and complex variables

## Let: an operator which produces 90 degrees counter clockwise

rotation of any vector to which it is applied as a multiplying factor.

A 3
= -A
A 2 -
= -A
2 A= -A A (-
1) = -A
2 = -1 -A
= - A

= imaginary
1

A4 = A
A( 2) (2)= A
A (-1) (-1) = A
A=A

## FORMS OF COMPLEX NUMBERS

-----------------------------------
1. Rectangular or Cartesian form
1.1trigonomitric form
2. polar form
3. exponential form
1. A = a + a rectangular form
Imaginary component
Real component

2. A = A / polar form

## converting polar to rectangular ( refer to the figure)

a
cos = ; a= A cos
A

a
sin = ; a1= A sin
A

A= a + a

## Simplifying, A= A ( cos + sin )

a1 a1
tan = ; = tan -1
( )
a a

RECTANGULAR TO POLAR

a1
2
A= a +()2

a1
= tan -1
( a )
3. A = A e exponential form

Example:
1. Give the polar and exponential form of vector A if A= 3+4.

A= 32+ 4 2 A= 5 53.13

polar
A= 5 A= 5 e 53.13
exponential form
4
= tan -1 (
3 )
= 53.13
-60
2. Give the rectangular form of vector A= 10 e

A= 5 -60o polar

a= 10 cos (-60o)

a= 5

## a1= 10 sin (-60o)

a1=-8-66

therefor: A=5-8.66

3. Evaluate 2010

= (4) 502
. 2
502
= (1) (-1)

2010 = -1

A= (5)2 +( 5)2
A = 7.07

= tan-1 ( 5
5 )

= 45o

## A = 7.07 180o +45o

A = 7.07 225o

VECTOR OPERATION

2. Subtraction
3. Multiplication
4. Division
5. Power
6. Root
7. Logarithm

Let A= a+a

B = b+b

## A+B = ( a+b) + ( a+b)

VECTOR SUBTRACTION

Let A = a+a

B = b+b
A-B = (a+a) (b + b)

## A-B = (a-b) + (a-b)

VECTOR MULTIPLICATION

Let A = A

B=B

A.B = ( A ) (B )

A.B = AB +

VECTOR DIVISION

Let A=A

B = B

A A< A
<
B = B< = B

POWER OF A VECTOR

An = ( A n

An = An n

ROOT OF A VECTOR

n A = n A <

n A = n A
n

LOGARITHM OF A VECTOR

Let : A = Ae

log e A = log e

By properties of logarithm,

log e A =
In A +

Sample problems.

A B C

7
A= 62 +72 tan -1
6 = 9.22 49.4o

## B= 5 cos 35o + 5sin 35o =4.1 + 2.87

180
C= = 0.765 rod = 43.83o
17 rod

## C= 7 cos 43.83o + 7 sin 43.83o

C= 5.05 + 4.85

D= ( 9.22 49.4 o
) (4.1 + 2.87 + 5.05 + 4.85)
D= (9.22 49.4o) (9.15 +7.72 )

## = (9.22 49.4o) ( (9.15)2 +(7.72)2 tan-1 ( 7.72

9.15 )

D= 110.36 89.55o

(6+3 )
2. Evaluate vector D if D = +8 30 o
\
(22 )

(6+3 )
D= +8 30o
(22 )

3
A= 62 +32 tan -1
( 6 ) = 6.71 26.56o

2
B= 2 +(2 )
2 2
tan-1 ( 2 ) = 2.83
45 o

## C= 8 30o = 8 cos 30o +8 sin 30o

C= 6.93 + 4
( 6.71<26.56 )2+ 6.93+ 4
D. 2.83<45
45.02<53.12 +6.93+ 4
= 2.83<45
= 15.91 <98.12 + 6.93 + 4
= 15.91 COS 98.12 + 15.91 SIN 98.12 + 6.93 + 4
= -2.25+ 15.75 + 6.93 + 4
D = 4.68 + 19.75
19.75
= ( 4.68 ) +(19.75)
2
tan -1 (
4.68
)

D= 20.296 <76.67

3. Evaluate vector H if
2
H = log e ( 3+4 ) [2 cis 30 +2<20 + 6 e ]
2 0 252

## ( 3+7) (5 cis 25) + (3<30)

Let
4
A = 3 + 4 = 3+4 < tan -1(
3
)

= 5 < 53. 13
B = 2 cos 30 + 2 sin 30
B = 1.732 +

## C=2 20 = 2 cos 20 + 2 sin 20

= 1.879 + 0.684

180
D = 0.252 rod 17 rod = 14.44

= 5.81 + 1.50

## E = 3+7 = 3+7 = 7.62 tan -1

( 73 )
E = 7.62 66.80

2
2 ( 5<53.13 ) [ 1.732+ +1.879+0.684 +5.81+1.50 ]
H = log e
( 7.62<66.80 ) (5< 25 ) +9<60

= log e

2 ( 25<106.26 ) (9.421+3.184 )
( 38.1<91.8 )+(9< 60 )

9.421
3.184

1
= log e
9.421+3.184 tan

( 25<106.26 )

2

= log e

2 ( 25<106.26 ) (9.94<18.67 )
3.3+ 45.87

248.5<124.93
2
= log e
3.3 + 45.87< tan1 ( 45.87
3.3 )

= log e
2 248.5<124.93
46< 85.89

= log e 2 5.40<39.04

## = log e 2.37 19.52 first root

19.52
= log e 2.32 e

rod
= log e 2.32 + 19.52 180

H = 0.84 + 0.34

4. ( 2x + 3y) -6-12 = 0
Solve for x and y.

## (2x) + 2 (2x) (3y) + (3y) = 6 + 12

4x + 12xy + 9y () = 6 + 12
(4x-9y) + 12xy = 6 + 12
4x - 9y = 6 1
12xy = 12
Xy = 1 2
1
Or x= 2

1
Substitute x = 2 to equation

4 ( 1y ) y =6
2
4
y - 9y = 6

[ 4
y ]
9 y =6 y

4- 9y = 6y

9y4 + 6y - 4 = 0

6 64 ( 9 ) (4 )
y = 2(81) x = 1.556

6 13.41640787
y = 2(9)

6 13.41640787
y(+) = 18

7.416407865
= 18

y = 0.412022659

y = 0.642

1 1
x=
=
y 0.6424

seatwork:

## [ ( 6+ 7 ) +10<60 ] [ 3 1000<60(6+ 8 ) ] +3e30

1. H = ( 6+ 2001 )+ 5< 35

## Ans. H = 1379.46 79.27

H =256.93 - 1355.32
2+ 14

2.
[ ( 12+16 ) ]
3

Ans: A = -0.0233- 0.021
A = 0.031 137.97

## ( 4+5 )2 ( 400+300 ) log e

3. H = (19+ 19 )210 e + 2005

4. H =

3 ( 3+ 4 )( 6+ 8 ) ( 2+2 ) (2+3 ) ( 43 )10 e 30
6 8 3+4 + 1216 100<60

## ( 6.4 <51.34 )2 3 500<36.87 100 e 0.5 n

H=
26.87<45 10 e 90 +
2005 = ( 4) 501
-
2005 =
( 40.96<102.68 ) 7.94 e 12.29 (4.605+0.5 )
= (5.18<22.5 10< 90 + )
4.605+0.5

=
[
( 40.96<102.68 ) 7.94 +12.29
rod
180 ]

( 40.96<102.68 ) ( 2.072+ 0.2145 )( 4.605+ 0.5 )
= 8.494 <55.708
85.44<111.85
= 8.494<55.708

H = 10.06 167.563

H = -9.824 + 2.17

## ( 3+ 4 )( 6+ 8 ) ( 2+2 )( 2+3 ) 4+3

5. H =
68 3+ 43 + 1216 100<60
10 e 30

203+0.524

= (124 +68 )( 2+3 ) ( 4 +3 )

3

35.956+22.708

2.302+0.524

=
3.162<26.5652.236<26.565+ 4.472<26.565
(124 +68 )

3

=
3 166.245<164.2
5.55<62.907

H= 3 29.954<227.107
H = 3.105 75.702
H= 0.767 +3

## Chapter 2 LAPLACE TRANSFORM

Laplace transformation is an operation, devoted by symbol L , which
associates with each function f (t), satisfying suitable conditions for t
O, a unique function F (s) called the laplace transform of f (t). by
definition,

L [ f ( t )] = F (s) = f ( t) e -8t
dt

## To take the inverse laplace transform,

f (t) = L -1 [ F(s)]

the laplace transform method solves differential equations and corresponding initial
and boundary value problems. The process of solution consists of there main steps.

## 1 . The given hard problem is transformed into a simple equation ( subsiding

equation).
2. The subsiding equation is solved by purely algebraic manipulations.
3. The solution of the subsiding equation is transformed back to obtain the
solution of the given problem.

## Laplace transforms reduce the problem of solving differential equation to

an algebraic problem.
PIERCE SIMON MARQUIZ DE LAPLACE was the great French mathematician
(1749-1827), professor in Paris and inventor of laplace transform. He
developed the foundation of potential theory and made important
contributions to celestial mechanics, astronomy in general, special
functions and probability theory.
OLIVER HEAVISIDE (1850-1925) the one who developed the powerful
practical laplace transform technique.

## LAPLACE TRANSFORM BASIC FORMULAS

Function Transform

(f (t)) F (s)
1
s
1
T s
2!
t S
n!
n
t n+1
(n = 0,1,.) s
(9+ 1)
Ta s 9+1
( a positive)
1
eat sa
1
cos cot s + w
w
sin cot s + w
s
cos h at s + a
a
sin h at s + a

## 1, Find the laplace transform of 1.

f (t) = 1
0

L {1} = f (t) e st
dt
0

L {1} = e-st dt
0

Let n = -st
Dn = -sdt

1
L{1} = s e-st

= [ 1 1
+
se se ]
1
L {1} = s

## 2. Find the laplacetransform of eat

0

at
L {e } = eat e-st dt
0

= e-(s-a)t dt
0

Let n = - (s-a) t
Dn = - (s-a) dt
dn
( sa) = dt
0
1
= - (sa) en dn
0
1 e9 sa
= - (sa) [ t ]

=-
1
( sa ) [ 1

1
e ( sa ) t e ]
1
L { eat } = sa

0

## Let: n= cos at dv= e -st dt

1
Dn= -sin at.adt v= s e-st

Dn= -a sin at dt
0

## Recall: ndv = nv- vdn

0

0
1 1
L {cos at} = cos at ( s e-st) - - s e-st ( - a sin at dt)
0

0
1 a
=- s cos at e-st - s sin at. E-st dt
0

st
Let: n = sin at dv = e dt
1
Dn = a cos at dt v=- s e-st

a cos at dt

=-
1
s cos at e st
-
a
s [ ( sin at
1
2
est )] -
s
1

=-
1
s cos at e -st |+s a sin at est| -
a
s cos at e-st dt
a sin at estscos est a a
= s - s cos at e-st (1 + s ) , cos at e-stdt =

at
a sin atcos
e-st

a s + a
1+ s = s

at
a sin ats cos est

Cos at e-st dt = s

## =t= [( a sin ats cos at

2 2
e st (s +a )

)(
a sin ( o ) s cos o
2
e ( s +a )
2 )]
Note for infinity limits
1. The maximum value of sin at = 1; therefore the highest angle we can
possibly assign is 90. It follows that at = 90.
2. The maximum value of cos at= 1; therefore the highest value of angle we can
possibly assign is 360. It follows that at = 360.

0
s
L {cos at} = cos e-st dt = s + a
0

## GAMMA FUNCTION OR GENERALIZED FACTORIAL FUNCTION is defined by the

equation:

(x) = e -st
tx-1 dt
0

=e-t v =t x-1
t
= e-t ( -1 ) t
1
= - e-t t v= x tx
v = v- v

(x) = e-t ( ) 1x
1
x
tx
0
tx (e-tt)

0 0
e
= x +1 e -t
txt
0 x 0

(x) = t [ t

o
x e xe ] +
1
x e
o
-t
t t

Comparison:
If (x) = x-1
(x-1) = x

1
(x) = x (x-1)

x (x) = (x-1)

Specifically

(1) = e -t 1-1
t t if x = 2
0

(1) = e -t
t (3) = 2 (2)
0

(3) = 2 (1)
let = -t (3) = 2
let = -dt
(3) = 2.1 = 21

(1) = e
( -) if x = 3
0

## = -e-t (4) = 3 (3)

0

= lim
t [ 1 1
+
e e ] (4) = 3 (3)

= 3.2.1
(1) = 1 = 3.2.1
Using equation A (4) = 31

## (x-1) = x (x) therefore:

if x=1
(x-1) = x 1
(2) = 1 (1)
(2) = 1 (1)
(2) = 1

Lets derive, L { t}

L { tn} = e st
tn dt
0

(n+ 1)
L { tn} = sn+1 or

n1
sn+1
Let: z = st
z
T= s
1
t = s dz

L { tn} = e
0
-z
( sz ) ( 1s )
n
dz

z dz
= e -z
- s . s
0

1
= s +1 e -z
.zn dz
0

## 5, Derive the laplace transform of sin h at.

1
By identifying: sin h at = 2 {eat e-at}

L {12 ( e at )} =
1
2 L {eat} -
1
2 L {e at
}
1
= 2 ( sa1 ) 12 ( s+1 a )
= 2
1
[ 1

1
sa s +a ]
= [
1 s+ as+ a
2 ( sa )( s+ a) ]
=
1
2 [ 2a
( sa ) ( s+a) ]
a
{ sin h at }=
L ( sa )( s +a)

## LINEARITY THEOREM ( linearity of the laplace transform

The laplace transform is a linear operation that is for any functions f (t) and g
(t) whose laplace transforms exist and any constants a and b.

Proof:
0

## By definition, L { a f ( t ) +b g(t )}= e st [ a f ( t ) +b g(t) ] dt

0

= a e st f ( t ) dt +b e st
g (t) dt
0 0

= a L { f (t ) }+b L { g(t) }
0

Example:
Find the laplace transform of cos h at.
1
at -at
Solution : Recall: cos h at = 2 (e + e )

## L {12 ( e at+ eat )} =

1
2 L {eat} +
1
2 L {e at
}

1 1 1 1
= ( ) ( )
+
2 sa 2 s+a
=
1
2 [ 1
+
1
sa s+ a ]
=
1
2 [ S +a+ sa
( sa ) ( s+a) ]
=
1
2 [ 2s
( sa ) ( s+a) ]
L {cos h at= s as }
THE GENERAL METHOD
Theorems 1. If f (t) is a continuous function of exponential order on [0, ]
whose derivative is also of exponential order and at least piece wise regular
on [0, ] , then :

## L {f (t) } = s { f (t) } f (0)

Proof:

L {f (t) } = f (t0 e st
dt
0

= lim [ f (t ) st
dt + e st
dt]
0 +

C 0
B

## Let : n = e-st dv = f (t) dt

Dn = -se-st dt n = f(t)

se
f ( t )(sest dt )
f (t) b b
[e st
f (t) t 0 st
dt ) + e st
f (t)
+ t 0

f (t)
(1) T = e sto
f (to) e s (0)
f (0) + s f (t ) e-st dt + [ e st
e sto f ( to ) ] +

s f (t ) e st
dt
+

+ s f (t ) e -st
dt
+

=L { f ' ( t)}=s f (t ) e st
dt f (0)
0

## Corollary 1. If both f (t) are continuous function of exponential order om

[ o, ] and f (t) is also of exponential order and at least piecewise

regular on [ o, ] then,

## Proof: this result follows immediately by applying theorem, twice to f (t):

L { f ' ' (t) }=L {[ f ' (t)] ' }=s L { f ' ( t)}f ' (o)

## =s [ s L { f (t)} f ( o)]f ' (o)

L { f ' ' ( t ) }=s L { f (t )}s f ( o )f ' (o)

## L { f ' ' ' (t) }=s L { f (t)} s 2 f ( o ) s f ' ( o )f n-1

(o)

(n-1)
Corollary 2: If f (t), f (t), f (t) .. f continuous and of exponential order on
[ o, ] and if f (n)
(t) is of exponential order and at least piecewise regular

on [ o, ], then
L { f (t ) }=s L { f (t) }s n-1
f (o) sn-2 f (o) f (n-1)
(o)

## ( refer for example to the next page ) A

Ex. Ay + by +ay = f (t); a,b,c are constants

## Solution: Take the laplace transform

a L { y ' ' }+ b L { y ' } +c L { y }=L { f (t) }

a [ s L { y } sy
y yy ' o ] +b [ s L { y } yy ] + c L { y }=L { f ( t ) }

## L { y } [ as +bs +c ] =L { f (t ) } + ( as+ b ) y+ ay '

L { f (t ) }+ ( as+b ) y+ ay '
L { y }=
as +bs +c

## INVERSE LAPLACE TRANSFORM

L -1 { F(s) } =f (t)

Example:

1. L -1
{ s +ww }=sin cot
2. L _1 { sa1 }=e at

## 3. What is the inverse laplace transform of

1
F (s) = s + 4 s+3

( s + 4s + 3 ) = (s +1) (s +3)

1 A B
= +
s + 4 s+3 (s +1) (s+3)
1 A B
=
s + 4 s+3 (s +1) + (s +3)

1 A ( s+3 ) + B( s+1)
=
s + 4 s+3 ( s+1 ) (s+3)

S= 0 = A+B ; A = -B
C= 1 = 3A + B
1
3A + B = 1 ; A=- 2
3 (-B) +B =1
1
-2B = 1 A= 2

1
B= 2

1 y y
=
s + 4 s+3 (s +1) - (s +3)

## L { s 41s+ 3 }= 12 L -1 ( s +11 ) 12 L -1 ( s +31 )

1 1
t
= 2 e - 2 e

L { s + 41s +3 }= 12 ( e e )

## 4. Solve : yn-y = t; y (0) = 1; y (0) = 1

First step: take the laplace transform

{ y } { y} = L {t }
L L
1
s Y (s)- sy (0) y (0) y (s) s
1
( s 1 ) y ( s )=s+1+
s

s+1 1
+
Y (s) = s 1 s (s 21)

s+1 1
+
= ( s+1 )( s1) s ( s21) for partial fraction

1 A B
=
+
s (s 21) s s 1

A ( s 21 ) + B(s 2 )
= 2
s (s 1)

For : S = 0 = A + B ; A= -B
Constant : 1 = - A
Therefore: A = -1 ; B = 1

1 1 1
= 2+
s ( s 1 ) s s 1
2

1 1 1
Y (s) = s+1
+
s 1 s

L -1 { y (s) }= L -1 { s+11 }+ L -1 { s 1
1
} -
L { s1 }
Y (t) = et + sin h t t

1. L { f ' ' ' ' (t) } =s L { f (t) }sf ( o ) s 2 f ( o )s f ' ' ( o )f '' ' (o)

2. L { f ' ' ' ' ' (t)}=s L { f (t) }s 4 f ( o )s f ' ( o )s2 f ' ' ( o )s f ' ' ' ( o )f ' '' ' (o)

## THE SHIFTING THEOREMS

One of the most useful properties of the laplace transformation is contained
in the so- called shifting theorem.
Theorem 1. ( s- shifting ) If F (t) is piecewise regular on [ o , ] and of
exponential order, then

L { eat f (t ) }= L { f (t) } s s +a

## L { eat f (t ) }= [ eat f ( t)] e st

dt
o

L { eat f (t ) }= f (t ) e (s+a) t
dt
o

## Corollary 1: L -1 { O(s) }=e at

L -1 { O( sa) }
s+a
{ eat cos bt }=
Formula 1: L ( s+a )2 +b
b
{ eat sin bt }=
Formula 2: L ( s+a )2+ b

(n+1)
{ eat t n }=
Formula 3: L ( s+ a ) n+1 n > -1

Example:

2 s+ 5
{ y }=
1. If L s +4 s +13 , what is y?

## By obvious manipulations, designed to make all occurrences of s involve the

same binomial, we have

s +20+1

L 2
{ y }=

1
-2t
Y=2e cos 3t + 3 e-2t sin 3t

## 2. Find the laplace transform of y.

t
Y + 2y + y = e ; y (o) = -1, y (o) = 1

## { y }sy y' o+2 [ s L { y } y ] + L { y }= L {et }

s L
1
{ y } [ s +2 s+1 ] = + sy+ y ' o+2 y
L s +1

1
{ y } [ s +2 s+1 ] = + s (1 ) +1+2(1)
L (s+1)2 s +1
1
{ y } [ s +2 s+1 ] = ( s+ 1)
L s +1

1 ( s+1)
{ y }=
L ( s +1 ) (s+1) (s +1)
1 1
{ y }=
L ( s+1) (s +1)

## From the formula:

I at
n
L t n e = ( s+a )
s +1

Y (t) =
1
2 L -1
{ 2
( s+ 1) } - L -1 1

1 t t
= 2 t2 e - e

1 t
Y(t) = ( 2 t2-1) e

## 3. What is the solution of the differential equation Y u+2y1 = t e t

for which Yo=1
and Y10 = -2.
1
[ s { y ( t ) }sy ( 0 ) y (0)] +2 [ s {Y ( t ) }Y ( 0 ) ] + {Y ( t ) }= ( s+1)
1
s{Y(t)} s(1) (-2) + 2s {Y(t)} 2(1) + {Y(t) = (s +1)
1
{ y (t ) } [ s +2 s +1 ] = +s
(s+1)
s+ 1+ 2 s+1
1
= +s
(s +1)
{ y (t ) }
1
{ y (t ) } = +s
(s +1)

(s +1)

1 1s
{ y (t ) } =
(s +1) + (s +1)
s +1

3 s
+ (s +1)
{ y (t ) } = 1
3

s s+11 (s+1) 1
A= = =
(s +1) ( s+1) (s +1) (s+ 1)

1 1

A= s+1 (s+ 1)

Y (t) =
1
31 -1
{ 3!
( s+1 ) 3+1}+ -1
{ s+11 } -1
1
(s +1)

t e
Y (t) =
+e te
3!

t
t+
6
Y (t) =

S- MULTIPLIED AND S DIVIDED TRANSFORMS

t

o

{ }
t
1
L f ( x ) dx =
L { f (t) }
o
s

## Proof: L { f (t) }= L { F ' (t )}= L { F(t) }F (o)

{ }
t o

L { f (t) }= s L f ( x ) dx f ( x ) dx
o o

{ }
t
1
L f ( x ) dx =
L { f (t)}
o
s

## Theorem 2. ( s- multiplied transforms)

If the inverse of (s) is a function f (t) which is continuous on [o,

## and of exponential order, if f (t) is at least piecewise regular on [o, and

of exponential order, and if f (o) =0,then the inverse of s (s) is f (t), that is,

d
L -1 { s (s ) }=f ' ( t )= L -1 { (s) }
dt

## Proof: L { f ' (t)}=s L { f (t) }f ( o ) =s (s)

L -1 {s ( s )=f ( t )= dtd }
'
L -1 { ( s) }

## Theorem 3. (s- divided transforms)

If the inverse of (s) is a function f (t) which is piecewise regular on [o,
t
and of exponential order, then the inverse of (s) /s is f ( x ) dx
o

{ }
t
1 1
Proof: L f ( x )dx =
L { f (t) }= ( s)
o
s s

L -1
{ 1
s o
}
(s) = f ( x ) dx

Example:

2
{ sin 2t }=
1. Given: L s + 4 , find

L -1 { s +s 4 }
To verify this result, we suppress the factor s, then use the given
formula to write the inverse of the remaining portion of the transform, getting

L -1 { s +s 4 }= 12 L -1 { s +2 4 }= 12 sin 2t
2t
1
d sin
2
F (t) = dt L -1

{ } 1
=
s + 4 dt
d

1
F(t) =
cos 2 t(2)
2

F(t) = cos 2t
2. L -1
{ 1
2
s(s + 4) }
1 1
Suppressing the factor s , we set (s) = s + 4

(s) =
1
{ }2
2 s + 4

L -1 { ( s) }=
1
2 L -1 { s +2 4 }= 12 sin 2t
Therefore:

L -1
{ 1
2
=
s(s + 4) o 2 }
sin 2 t
dt

t
1
= sin 2t dt
2 o ; let : n = 2t

Dn = 2dt
dn
=dt
2
t
1 dn
=
2 o
sin
2

2t
t

cos
= t
o

1 1

4 o
sin n dn=
4

1 1
=- 4
cos 2 t+ cos (o)
4
1 1
=
cos 2t
4 4
L -1
{ 1
=
s(s + 4) 2
2 } (
1 1cos 2 t
2 )
1cos 2
By identify :
=sin
2
Finally:

L -1
{ 1 1
}
= sin t
s(s + 4) 2
2

## Theorem 1: ( Transform Differentiation)

If f (t) is piecewise regular on [ o, and of exponential order, and if

Proof:

## By definition we have { f (t) }= f ( t ) e st

dt = (s), and by differentiating
o

this,

d
f (t ) e
ds o
st
dt = (s)

d
f (t ) ds
( est ) dt= [ t f ( t ) est dt=' ( s) ]
o o

{ tf (t) }=' (s )

By taking inverses in the assertion of theorem and then solving for f (t),

Corollary 1:

If { f (t) }= ( s ) , then

1
F (t)= -1 { (s) }=
t
-1 {' (s )}
1
The inverse of a transform is equal to - t times the inverse of the

## derivative of the transform.

Example 1: What is the laplace transform of
F (t) = t sin at ?

{ t sin at }=
d
ds
[ {sin at } ] =
d
[
a
ds s +a ]
2 as
{ t sin at }=
(s + a2)
2

(s+ 1)
Example 2: What is y if { y }= ( s )=
(S1)
By corollary 1, theorem 1

Y=- t
1
-1 { (
d

s+1
ds a1
=
1
t )} -1 { s+11 s11 }
e e 2 sin h t
Y=
=
t t

## Ty -2 ( t+1 ) y ' + ( t+2 ) y=0

d ' d d
- ds [
s y ( s )sy y o ]+ 2 [ sy ( s ) y ] 2 [ sy ( s ) y ] y ( s ) +2 y ( s ) =0
ds ds

d
2 [ sy ( s ) y ] ds y ( s ) +2

(s 2+ 2 s1 ) y ' ( s ) + (4 s+ 4 ) y ( s )=3 y

'
- ( s 2 s+1 ) y ( s )4 ( 4 s1 ) y ( s )=3 y

'
- ( s1 ) y ( s ) 4 ( s1 ) y ( s )=3 y
4 ( s1 ) y ( s) 3 y
Y (s) - =
(s1) (s1)

4 3 y
y=
Y (s) s1 (s1)

dy
Recall:
+ y P ( x )=Q ( x )
dx

1. F = P ( x ) dx
Y (1.f) Q ( x ) [ ( 1. f ) ] dx +c

4 ds
e (s1) =e 4lu (s-1)
= (s-1)4

f = (s-1)4
after multiplying each side by this factor and integrating, we have

( s1 )4 y = y ( s1 ) + c

y c
+
Y (s) = s1 (s1)

c
Y(t) = y et +
t e
6

3 y
y [ 1( s1 ) ] = [ 1(s1) ] ds +c
A. (s1)

( s1 )4 y =3 y ( s1 )2 ds +c

4 (s1)
( s1 ) y = y +c
2+1

( s1 )4 y = y ( s1 ) +c
Theorem 2:
Fi F (t) is piecewise regular on [o, and of exponential order, if {f
(t)} = (s) and if f (t)/t has a limit as t approaches zero from the right,
then

{ }
f (t)
t
= ( s ) = { f (t) } ds
0 o

proof:

(s) = { f (t) }= f ( t ) e st
dt
o

## Hense integrating from s to , we obtain

[ ]

( s )= f ( t ) est dt ds
o o o

## Under the assumption that

t-o [ ]
f (t)
t

( s ) ds= f ( t ) e
o o o
st
ds dt = f (t )
o
[ ]
e
t
dt

=
o
[ ]
f (t)
t
e d t

= { }
f (t )
t

By taking inverses in the assertion of theorem and then solving for f (t) , we
obtain
Corollary 1: if { f (t) }= ( s ) , then

{ }

## F (t) = { (s) }=t ( s ) ds

o

If words: Corollary 1:

## The inverse of a transform is equal to t times the inverse of the

integral of the transform from s to .

Example 1:

What is {sint kt } ?

{sint kt }= {sin kt } ds

k s
= s +k
ds=tan
k s
o

=s- [ s
tan tan
k
s
k ]
s s
=
tan =cot
2 k k

Example 2:
s
{ y }=
What is y if 2
( s 1)
2
s 1
2
1
Y = t

{ }

s
(s 21)
ds =t
o

s 21
2
= t 1

= t {( 1 1

1
4 s1 s+ 1 )}
t
y= ( e e )
4
ee
recall: sin ht = 2

t e e
y= 2 ( 2 )
t sin ht
y= 2

## solving for the identity of example 1:

3
=
tan k
90
K 2

=tan ( ks )
+=90
=90

=90tan 1 ( ks )
But:
k
tan
=
s

1 k
=
cot s

=cot ( ks )
Therefore:

=90tan 1 ( ks )
cot ( ks )= 2 tan ks1